Formaldehyde-activated WEHI-150 induces DNA interstrand crosslinks with unique structural features. Issue 3 (1st February 2020) - Pumuye, Paul P.; Evison, Benny J.; Konda, Shyam K.; Collins, J. Grant; Kelso, Celine; Medan, Jelena; Sleebs, Brad E.; Watson, Keith; Phillips, Don R.; Cutts, Suzanne M.
Graphical abstract: Abstract: Mitoxantrone is an anticancer anthracenedione that can be activated by formaldehyde to generate covalent drug-DNA adducts. Despite their covalent nature, these DNA lesions are relatively labile. It was recently established that analogues of mitoxantrone featuring extended side-chains terminating in primary amino groups typically yielded high levels of stable DNA adducts following their activation by formaldehyde. In this study we describe the DNA sequence-specific binding properties of the mitoxantrone analogue WEHI-150 which is the first anthracenedione to form apparent DNA crosslinks mediated by formaldehyde. The utility of this compound lies in the versatility of the covalent binding modes displayed. Unlike other anthracenediones described to date, WEHI-150 can mediate covalent adducts that are independent of interactions with the N-2 of guanine and is capable of adduct formation at novel DNA sequences. Moreover, these covalent adducts incorporate more than one formaldehyde-mediated bond with DNA, thus facilitating the formation of highly lethal DNA crosslinks. The versatility of binding observed is anticipated to allow the next generation of anthracenediones to interact with a broader spectrum of nucleic acid species than previously demonstrated by the parent compounds, thus allowing for more diverse biological activities.